Socioeconomic Determinants of Participation in Cancer Screening in Argentina: A Cross-Sectional Study - Nuche-Berenguer, Bernardo; Sakellariou, Dikaios (Frontiers in Public Health, 2021)
Low socioeconomic status is associated with late cancer diagnosis and mortality in Argentina. It is important that cancer screening services are accessible to the whole population so that cancer can be detected early. Our aim in this study was to investigate socioeconomic determinants for the disparities in the use of breast, cervical, and colorectal cancer screening services in Argentina, and to measure the country progress in reducing differences in cancer screening participation across socioeconomic levels. We performed a secondary analysis of cross-sectional data from the 2018 National Survey of Risk Factors of Argentina. The sample included data from 49,170 households. We also compared the results with data from the 2013 wave of the same survey in order to assess progress on cancer screening participation across income and education categories. Income, education, health insurance, disability, and marital status were associated with cancer screening underuse in Argentina. Comparison between 2013 and 2018 demonstrated that there has been some progress towards increasing cancer screening uptake, but this increase is not equitably distributed across the population. To further reduce disparities in cancer participation across socioeconomic levels, cancer screening programs in Argentina should reinforce strategies to become more accessible to all. It is important to proactively reach those populations that are underusers of cancer screening and ensure that barriers that stop people from accessing cancer screening are explored and adequately addressed.